2020
DOI: 10.1186/s13256-020-02401-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow up after denosumab treatment for osteoporosis – rebound associated with hypercalcemia, parathyroid hyperplasia, severe bone mineral density loss, and multiple fractures: a case report

Abstract: Background: The rebound effect after stopping treatment with denosumab may be associated with rapid loss of the gains in bone mineral density achieved with treatment, high levels of bone remodeling markers, the occurrence of vertebral fractures, and even hypercalcemia. Case presentation: A 64-year-old osteoporotic Caucasian woman suffered from a fracture of her second lumbar vertebra in 2004. From January 2005, she was treated with denosumab for 9 years, with good densitometry results for her hip and lumbar ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Calcium carbonate and alfacalcidol can be considered to inhibit the rebound of iPTH and avoid an excessive decrease in serum calcium when the patient has hypocalcemia. As shown in literature, maybe it is timing of vitamin D and calcium supplements in the first 2 weeks especially finding calcium decrease to the lower limit of normal range 17 . The most appropriate time of vitamin D and calcium supplements after denosumab administration still needs more research.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Calcium carbonate and alfacalcidol can be considered to inhibit the rebound of iPTH and avoid an excessive decrease in serum calcium when the patient has hypocalcemia. As shown in literature, maybe it is timing of vitamin D and calcium supplements in the first 2 weeks especially finding calcium decrease to the lower limit of normal range 17 . The most appropriate time of vitamin D and calcium supplements after denosumab administration still needs more research.…”
Section: Discussionmentioning
confidence: 96%
“…As shown in literature, maybe it is timing of vitamin D and calcium supplements in the first 2 weeks especially finding calcium decrease to the lower limit of normal range. 17 The most appropriate time of vitamin D and calcium supplements after denosumab administration still needs more research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent RCT, treatment with denosumab or alendronate for 12 months improved BMD and did not affect the health of blood vessels (including scores of VC) in patients on dialysis [ 145 ]. Several studies showed that the fracture risk increases after discontinuation of denosumab in osteoporotic women with normal kidney function [ 179 , 180 , 181 , 182 , 183 , 184 ]. Studies addressing this concern in CKD are lacking.…”
Section: Prevention and Treatment Of Adb In Ckdmentioning
confidence: 99%
“…Based on these findings and earlier reports in literature, a diagnosis of exclusion of severe hypercalcaemia as a result of rebound hyperactivation of osteoclasts after discontinuation of denosumab was put forward. [5][6][7][8] The origin of the acute kidney injury was related to the profound hypercalcaemia. Hyperhydration and a low-calcium diet were initiated which was followed by a partial recovery of the kidney function (eGFR 74 ml/min/m 2 ).…”
Section: Treatment Of Central Giant Cell Granuloma With Denosumab: a ...mentioning
confidence: 99%